Pengaruh Macam Komposisi Media Tanam dan Dosis Vermikompos Cair terhadap Pertumbuhan dan Hasil Tanaman Selada ( Lactuca sativa L.) Secara Hidroganik - Muhammad Fikri Aziz; Indiyah Murwani; N Nurhidayati (Folium : Jurnal Ilmu Pertanian, 2020)
With decreasing the area of productive agricultural land, soilless cultivation is greatly needed to develop healthier vegetables cultivation. This study aimed to determine the effect of the kind of composition of the growing medium and liquid vermicompost dosage on the growth and yield of lettuce (Lactuca sativa L.) which growing hidroganically. This study was a pot experiment using Factorial Randomized Block Design (RBD). The first factor was the kind of media composition consisting of two levels, namely: M1 = cocopeat (55%), zeolite (15%), and sand (30%), M2 = cocopeat (55%), zeolite (30%), sand 0.14 (15%). The second factor was vermicompost dosage consisting of five levels: V1 = 50 g/pot, V2 = 100 g/pot, V3 = 150 g/pot, V4 = 200 g/pot, V5 = 250 g/pot. Each treatment had thre replications with five plants samples. The results showed that the two factors tested did not show significant interaction. Separately, the kinds of media composition did not have a significant effect. While the treatment of vermicompost dosages had a significant effect, where  overall the dosage of V4-V5 (200-250 g/pot) gave the highest yield of lettuce. The average fresh weight of total biomass at these doses ranged from 158.92-163.33 g/plant. Keywords: Composition of growing media, Lettuce, Hydroganic, Vermicompost